The CopA2-Type P1B-Type ATPase CcoI Serves as Central Hub for cbb3-Type Cytochrome Oxidase Biogenesis - Andrei, Andreea; Di Renzo, Maria Agostina; Öztürk, Yavuz; Meisner, Alexandra; Daum, Noel; Frank, Fabian; Rauch, Juna; Daldal, Fevzi; Andrade, Susana L. A.; Koch, Hans-Georg (Frontiers in Microbiology, 2021)
Copper (Cu)-transporting P1B-type ATPases are ubiquitous metal transporters and crucial for maintaining Cu homeostasis in all domains of life. In bacteria, the P1B-type ATPase CopA is required for Cu-detoxification and exports excess Cu(I) in an ATP-dependent reaction from the cytosol into the periplasm. CopA is a member of the CopA1-type ATPase family and has been biochemically and structurally characterized in detail. In contrast, less is known about members of the CopA2-type ATPase family, which are predicted to transport Cu(I) into the periplasm for cuproprotein maturation. One example is CcoI, which is required for the maturation of cbb3-type cytochrome oxidase (cbb3-Cox) in different species. Here, we reconstituted purified CcoI of Rhodobacter capsulatus (R. capsulatus) into liposomes and determined Cu transport using solid-supported membrane electrophysiology. The data demonstrate ATP-dependent Cu(I) translocation by CcoI, while no transport is observed in the presence of a non-hydrolysable ATP analog. CcoI contains two cytosolically exposed N-terminal metal binding sites (N-MBSs), which are both important, but not essential for Cu delivery to cbb3-Cox. CcoI and cbb3-Cox activity assays in the presence of different Cu concentrations suggest that the glutaredoxin-like N-MBS1 is primarily involved in regulating the ATPase activity of CcoI, while the CopZ-like N-MBS2 is involved in Cu(I) acquisition. The interaction of CcoI with periplasmic Cu chaperones was analyzed by genetically fusing CcoI to the chaperone SenC. The CcoI-SenC fusion protein was fully functional in vivo and sufficient to provide Cu for cbb3-Cox maturation. In summary, our data demonstrate that CcoI provides the link between the cytosolic and periplasmic Cu chaperone networks during cbb3-Cox assembly.